(untitled) (The Peerian Journal, 2023)
The article presents an extended analysis of existing approaches and opportunities for the use of innovative technologies, devices, equipment and mobile applications in sports and physical education classes in higher educational institutions. Based on it, the possibilities of using gadgets in the field of monitoring the level of physical health and assessing the sports achievements of students are considered. Modern trends in the development of education require the systematization of existing materials, study of the concept and system of introduction of modern technologies based on information flows (gadgets), means and devices in the educational process in physical education classes.